2021
DOI: 10.1186/s40816-021-00277-1
|View full text |Cite|
|
Sign up to set email alerts
|

Attenuation of glycation and biochemical aberrations in fructose‐loaded rats by polyphenol‐rich ethyl acetate fraction of Parkia biglobosa (jacq.) Benth. (Mimosaceae) leaves

Abstract: Background Different parts of the Parkia biglobosa plant are employed in traditional medicine in different African communities. However, information ratifying its use and biochemical influence on health is still scanty in literature. Thus, the present study assessed the influence of the ethyl acetate fraction of Parkia biglobosa leaves (EAFPB) on some biochemical parameters of sub-chronic fructose-loaded rats. Methodology Twenty-five Wistar rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our earlier study had shown the beneficial effect of this fraction (PBF) in attenuating biochemical aberrations in high fructose-loaded rats as well as its rich polyphenolic profile as detected using Gas chromatography coupled with a flame ionization detector. 15 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging assay measures the free radical-quenching capability of various antioxidant compounds while the FRAP assay measures antioxidant molecules' ability to reduce Fe 3+ to Fe 2+ . 10 The in vitro antioxidant result (Table 1) showed that radical-scavenging activity (IC50 = 0.47 mg/ml) as well as Fe 3+ reduction increased with increasing concentration indicating good antioxidant properties of the fraction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our earlier study had shown the beneficial effect of this fraction (PBF) in attenuating biochemical aberrations in high fructose-loaded rats as well as its rich polyphenolic profile as detected using Gas chromatography coupled with a flame ionization detector. 15 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging assay measures the free radical-quenching capability of various antioxidant compounds while the FRAP assay measures antioxidant molecules' ability to reduce Fe 3+ to Fe 2+ . 10 The in vitro antioxidant result (Table 1) showed that radical-scavenging activity (IC50 = 0.47 mg/ml) as well as Fe 3+ reduction increased with increasing concentration indicating good antioxidant properties of the fraction.…”
Section: Resultsmentioning
confidence: 99%
“…14,24 Thus, the antioxidant effect observed in the in vitro study could be a result of the phenolic constituents of the plant sample as earlier reported. 15 Over-activity of enzymes such as α -amylase and α -glucosidase is one of the contributors to post-prandial hyperglycemia. 25 Thus, mild inhibition of the activities of these enzymes is a therapeutic strategy for managing diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations